ChemInform Abstract: Simplest N‐Sulfonylamine HNSO2. Issue 52 (6th December 2016) - Deng, Guohai; Wu, Zhuang; Li, Dingqing; Linguerri, Roberto; Francisco, Joseph S.; Zeng, Xiaoqing
Abstract: Flash vacuum pyrolysis of MeOS(O)2 N3 (caution: potentially hazardous and explosive) results in the formation of HNSO2 in the gas phase.